Survey nurses’ collaboration in clinical decision making - Lili Rostamnia; Ezzat Paryad; Ehsan Kazem Nejad Leili; Afsaneh Pasha (Journal of Holistic Nursing and Midwifery, 2011)
Introduction: Nurses are the largest care delivering group. They have to judge in clinical ‎setting and by team work detect and solve patients problem in nursing function domains. ‎Collaboration in decision making helps this function. ‎